Analysis of a restriction endonuclease map for bovine papillomavirus type 2 DNA. Issue 3 (March 1981) - Potter, Harold L.; Murphy, Michael F.; Abraham, John M.; Morgan, Don M.; Meinke, William J.
Abstract : A physical map was constructed for bovine papillomavirus type 2 DNA by the use of restriction endonucleases. A comparison between the genomes of bovine papillomavirus types I and 2 in regard to location and number of cleavage sites of seven enzymes is also presented. This comparison revealed similarities between the two genomes.